Plasmapause location under quiet geomagnetic conditions (Kp ≤ 1): THEMIS observations. Issue 18 (30th September 2015) - Kwon, H.‐J.; Kim, K.‐H.; Jee, G.; Park, J.‐S.; Jin, H.; Nishimura, Y.
Abstract We statistically examined the plasmapause location (Lpp) under quiet geomagnetic conditions (Kp ≤ 1) using the electron density inferred from the Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft potential for 2 year period (2008 and 2009). Five hundred forty‐three Lpp samples were identified under steady quiet conditions with Kp values ≤ 1 during 12 h prior to the plasmapause crossing. From our large data set, we determined the medians and means of Lpp in L and magnetic local time (MLT). They are located near geosynchronous orbit and nearly circular. The Lpp medians show a slight bulge located in postdusk sector. Comparing with previous models, our median or mean Lpp is extended ∼1–2 L from the Earth than the model Lpp along the local time from 0800 to 2400 MLT. That is, Lpp locations in the previous models are underestimated during quiet geomagnetic conditions.